An Honour For Sabahans Says V-C - The Star, (2008)
Prof Datuk Dr Kamarulzaman Ampon, the first Sabahan to be made vice-chancellor of Universiti Malaysia Sabah (UMS) has described his appointment as an honour to the people of the state.